ETHNOMATHEMATICS FOR ELEMENTARY SCHOOL STUDENTS IN KEBUMEN REGENCY USING CORN PLANT MEDIA - Abdul Aziz; Iswahyudi Joko Suprayitno; Rully Cahritas Indra Prahmana; Puguh Prasetyo (Universitas Muhammadiyah Semarang, 2021)
This article aims to find out design research and explore the potential for developing local culture-based learning methods for elementary school students in Kebumen district. This paper describes the concept of ethnomathematics-based design research at SD N Tambaksari, Kebumen Regency, Central Java in improving literacy and numeracy skills. Literacy and numeracy skills are indicators that need to be strengthened. The basic research design used is a research design that describes learning activities using local culture-based learning media or games with corn plants. The media used is by using food culture in the form of corn with abundant availability. The use of corn seeds is used by 2nd grade students of SD N Tambaksari to learn arithmetic operations. There are two aspects to be considered in this activity, namely literacy and numeracy. At the time of learning students are also invited to observe learning videos about arithmetic operations for further Based on these activities students are more active in participating in learning. Learning based on local food culture that can be applied in campus teaching programs to strengthen the literacy and numeracy aspects of students. Keywords: design research, ethnomathematics, traditional games